2017
DOI: 10.3233/jad-161109
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cognitive Decline in Dementia with Lewy Bodies in a Large Multicenter, International Cohort

Abstract: Background & Objective The aim of this study was to describe the rate and clinical predictors of cognitive decline in dementia with Lewy bodies (DLB), and compare the findings with Alzheimer’s disease (AD) and Parkinson’s disease dementia (PDD) patients. Methods Longitudinal scores for the Mini-Mental State Examination (MMSE) in 1290 patients (835 DLB, 198 PDD and 257 AD) were available from 18 centers with up to three years longitudinal data. Linear mixed effects analyses with appropriate covariates to mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
58
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 27 publications
(24 reference statements)
12
58
2
1
Order By: Relevance
“…13 In this framework, a work package was devoted to the retrospective collection of functional imaging studies (FDG PET and DAT SPECT) of probable DLB patients with the aim of creating a repository hosted in the core laboratory at the Genoa center. 13 In this framework, a work package was devoted to the retrospective collection of functional imaging studies (FDG PET and DAT SPECT) of probable DLB patients with the aim of creating a repository hosted in the core laboratory at the Genoa center.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 In this framework, a work package was devoted to the retrospective collection of functional imaging studies (FDG PET and DAT SPECT) of probable DLB patients with the aim of creating a repository hosted in the core laboratory at the Genoa center. 13 In this framework, a work package was devoted to the retrospective collection of functional imaging studies (FDG PET and DAT SPECT) of probable DLB patients with the aim of creating a repository hosted in the core laboratory at the Genoa center.…”
Section: Methodsmentioning
confidence: 99%
“…13 Given the retrospective nature of the present study, diagnosis of probable DLB was originally made according to diagnostic criteria for probable DLB as defined by McKeith et al in 2005. 13 Given the retrospective nature of the present study, diagnosis of probable DLB was originally made according to diagnostic criteria for probable DLB as defined by McKeith et al in 2005.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the great majority of subjects with both ADD and LBD, this co-existence is recognized only at autopsy [41,[112][113][114][115], currently preventing, except for the minority with clinically-typical DLB, the exclusion or stratification of LBD subjects within ADD clinical trials.The presence of LBD in ADD is clearly of clinical significance. Multiple autopsy-validated studies have indicated that cognitive decline is faster in ADD with any degree of associated LBD [26,[42][43][44][45]. Formerly, it was not apparent whether or not this was primarily driven by dementia with Lewy bodies (DLB) subjects with neuropathologically-severe LBD (mostly neocortical stage diffuse Lewy body disease), as disease duration is reportedly shorter in this group [109,116].…”
mentioning
confidence: 93%
“…If all neuropathological changes found in elderly brains were considered, there would be few if any cases of "pure" ADD. While not all of these aging changes are likely be clinically significant [37], several of the commonly-observed ADD comorbidities have been demonstrated to contribute to cognitive impairment, including Lewy body disease (LBD) [4,23,26,30,[41][42][43][44][45][46][47], hippocampal sclerosis [29,[47][48][49][50][51][52], 13,37,[53][54][55][56][57] and cerebral infarcts [1,10,11,30,35,46,57,58,[58][59][60][61][62][63][64][65][66][67][68][69][70]. Aside from causing increased variability in clinical response, it is possib...…”
mentioning
confidence: 99%